PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KANTOR CAMAT TELUKDALAM KABUPATEN NIAS SELATAN - Erna Selvia Zebua (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
The aim of this research is to determine the influence of leadership style and work motivation on employee work productivity at the Telukdalam Subdistrict office, South Nias Regency. This type of research is quantitative. The population was all employees totaling 33 respondents while the sample used a saturated sampling technique with a population of 33 people so the entire research sample was used. This type of research data is primary data, namely data obtained directly from respondents. The data source for this research is from consumers using a questionnaire. The data analysis method used is multiple regression analysis. Based on the research results, it was determined that there was a partial influence of leadership style on employee work productivity at the Telukdalam Subdistrict office, South Nias Regency, and there was a simultaneous influence of work motivation on employee work productivity at the Telukdalam Subdistrict office, South Nias Regency. The suggestions of this research are (1) It is hoped that superiors will provide adequate training and ensure that each employee understands their duties and responsibilities clearly. Apart from that, it is necessary to implement a strict monitoring system to help or prevent errors. (2) It is hoped that superiors and employees will need to increase efficiency in managing time and increase work motivation.